Implication of Q-pop phenomenon in Kazakhstan: an exploration of strengths and opportunities (Journal of Philosophy Culture and Political Science, 2023)
Abstract: This article explores the transformative impact of Q-pop, a prominent cultural phenomenon in contemporary Kazakhstani popular music, on Kazakhstan’s culture and music industry. The study traces Q-pop’s development to the boy band named Ninety One. It examines its impact on Central Asian regions and their pop culture and entering the Russian market. The research uses SWOT analysis to explore factors behind Q-pop’s rise, its connection with youth, and national identity. The study envisions opportunities for local musicians, international recognition, and continued growth. Additionally, Q-pop’s influence has extended to neighboring regions, as seen with the emergence of KG-pop/Z-pop in Kyrgyzstan and boy bands with all Kazakh members in Russia. This research aims to understand this transformative phenomenon’s effects on Kazakhstan’s identity and music industry, guiding strategic plans for its expansion. The research methodology utilizes SWOT analysis, exploring Q-pop’s impact on culture and music through internal strengths and weaknesses and external opportunities and threats. This approach offers insights into Q-pop’s position, potential, challenges, and growth strategies, informing decision-making. Q-pop’s strengths include diverse audience reach, cultural authenticity, and emotional connection due to cultural proximity. Weaknesses involve intellectual property protection, limited infrastructure, and competition scarcity. Opportunities encompass promoting Kazakh culture globally, penetrating non-USSR markets, and emulating K-pop strategies. Threats include emerging Central Asian genres, Russian dominance, geopolitical tensions, and political instability. Q-pop’s SWOT analysis reveals its potential and challenges. Stakeholders must capitalize on strengths and opportunities while addressing weaknesses and threats. Learning from K-pop, Kazakhstan can promote Q-pop as a soft power, strengthening its global influence. By leveraging Q-pop’s strengths and opportunities and mitigating weaknesses and threats, Kazakhstan can position Q-pop as a successful cultural export. The article concludes with recommendations for stakeholders, emphasizing support for Q-pop’s growth as a soft power strategy to elevate Kazakhstan’s global reputation, cultural influence, and economic prospects. Keywords: Q-pop, Kazakhstan, SWOT analysis, music industry, soft power, Kazakh popular music.